Characterization and process development for the selective removal of Sn, Sb, As from anode slime obtained from electrolytic copper refining - Steinlechner, Stefan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The present research paper describes the characterization of anode slime with regard to the disturbing elements Sn, As, Sb in the processing for a precious metals recovery and a proposal for a process concept to remove and recover separate and enriched streams of As, Sn and Sb. First, the anode slime was characterized concerning its constituents and morphology using scanning electron microscopy, hence forming the base for the process development. Subsequently, a hydrometallurgical leaching concept with alkaline media, a 4 mol/liter potassium hydroxide solution, was investigated to separate the mentioned metals in separate streams.